The production of graphene nano layers by using millingexfoliation hybrid process - Guler, S. Hale; Guler, Omer; Evin, Ertan (Taylor & Francis Inc, 2017)
Even though high quality graphene can be produced through chemical exfoliation of Graphite or Expanded graphite (EG), the amount of acquired products is limited. Graphite powders were subjected to a pre-milling process with prevailing shear stress in order to increase the amount of products. Therefore, separation of hexagonal layers through pre-separation process was targeted. The milled powders were firstly mixed in the saturated acid mixture containing H2SO4 and HNO3, and then heated to 950 degrees C. At the end of process, the distance between layers was expanded and the structure called as expanded graphite was obtained. Separation of layers and formation of graphene were provided by stirring expanded graphite within a chemical solvent for a while. The obtained samples were examined by using X-ray analysis, electron microscopy analysis, and Raman spectroscopy analysis. Despite the fact that there is a production method for graphene by chemical exfoliation, addition of the milling into steps of this process is an unusual step. Although a great amount of amorphous structures occurred in the structure at the end of milling process in this study, there were still graphitic structures preserving its hexagonality in the sample even if just a little. Most of amorphous carbon was removed from the structure as a result of applying further steps of process to milled graphite. A great part of graphitic structures apart from amorphous carbon structures were transformed into graphene. Even though amorphous carbon structures and defects were still found in the product, the obtained graphenes were relatively qualified and of high amount.
Keywords: graphene; exfoliation; ball milling